(untitled) (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to the description of the carnival aesthetics of the modern language field in which the laughter beginning comes to the first place and a new correlation of festive and everyday life, real and fantastic, normative and non-standardare being created. Carnivalization is characterized as an «inversion of binary oppositions», upturning of the meaning of binary oppositions of Russian language. The analysis has demonstrated that to display the ideas of carnivalization all resources of language are being used, big opportunities give the lexical units such as synonyms, antonyms, homonyms, paronyms, ambiquous words, calembour use of which brings to unexpected semantic shift and actualization of occasional components; an expressive potential of Russian derivation is actively being used and graphic and phonetic neoplasms become very popular as well.The held analysis of various methods of carnivalization allows us to state that a game strategy of communication has become a leading one in the modern communication discourse; appeareda new semantic field with carnival aestheticswhich often breaks down the usual stereotypes and builds up a new humorous picture of the world in the consciousness of native speakers.